EARNINGS QUALITY AND COVID-19 OUTBREAKS IN INDONESIA - Anwar, Yuli; Djan, Ismulyana; Mulyadi, Dedy; Wihananto, Adri (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2024)
Earnings quality is a critical indicator and an important element of a company's financial statement performance especially in the COVID-19 Outbreaks. This research aims at proving whether there was a difference in earnings quality before and during the COVID-19 Outbreak. The scope of this research was restricted to LQ-45 firms and the final sample in the observation period was 166 from 584 observations for the period 2010-2022. The sampling technique used purposive sampling and hypothesis testing used the independent T Test method. This research found that earnings quality on LQ-45 in the Indonesia Stock Exchange during the COVID-19 outbreak had higher earnings quality than before the COVID-19 outbreak. Therefore, it was feasible that other rising countries' results might differ from those of Indonesian firms. The results of this research were used to help investors make investment decisions.